The effects of voltage subharmonics on cage induction machine. (October 2019) - Gnaciński, P.; Hallmann, D.; Pepliński, M.; Jankowski, P.
Highlights: Load properties significantly influence windings temperature under subharmonics. Induction motors are especially exposed to overheating for small moments of inertia. Power quality standards require revision. Abstract: This paper deals with the influence of load properties on undesirable phenomena occurring in an induction motor supplied with voltage containing subharmonics. The results of calculations with a hybrid field-circuit method are experimentally verified and presented for a totally enclosed fan-cooled cage induction machine of 3 kW rated power. The results of research show that motor currents, power losses, and windings temperature significantly depend on moment of load inertia, and in much less degree, on a torque-speed characteristic. For small moments of load inertia and some frequencies of voltage subharmonics are observed especially high amplitudes of current subharmonics and particularly significant increases in power losses and windings temperature.